Study on porphyrin/ZnFe2O4@polythiophene nanocomposite as a novel adsorbent and visible light driven photocatalyst for the removal of methylene blue and methyl orange. (July 2018) - Kharazi, Parnian; Rahimi, Rahmatollah; Rabbani, Mahboubeh
Highlights: A new magnetically responsive three-component nanocomposite was successfully prepared. First, ZnFe2 O4 nanoparticles were synthesized and coated with polythiophene to prepare ZnFe2 O4 @Polythiophene. Subsequent, ZnFe2 O4 @Polythiophene was sensitized with a prophyrin (TCPP) to prepare TCPP/ZnFe2 O4 @Polythiophene. Removal efficiency of methyl orange (MO) and methylene blue (MB) was investigated in presence of prepared nanocomposite. The synthesized nanocomposite shows excellent photocatalytic and adsorption activity for MO and MB, respectively. Abstract: A new magnetically responsive three-component nanocomposite consisting of ZnFe2 O4 (ZnFe), polythiophene (PTh) and porphyrin was successfully prepared by coating of ZnFe2 O4 nanoparticles with polythiophene and subsequent sensitizing with tetrakis(4-carboxyphenyl)prophyrin (TCPP). The prepared TCPP/ZnFe2 O4 @Polythiophene nanocomposite (TCPP/ZnFe@PTh NC) was investigated by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), Energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy imaging (SEM) and vibrating sample magnetometer (VSM). Diffuse reflectance spectroscopy (DRS) was used to find the photocatalytic ability of this nanocomposite. In addition, photocatalytic–adsorption activities of prepared samples were carried out for removal of methyl orange (MO), methylene blue (MB) and mixture of MB and MO under visible LED lamp light and sunlight irradiation. The results indicated that the synthesized nanocomposite not only shows excellent photocatalytic and adsorption activity for removal of MO and MB, respectively, but also can be separated easily by an external magnet and reused twice more.